Optimization of Village Budget Plan Selection Based on Priorities Using Method Promethee and Borda - Dwi Yanti Laily; Muhammad Dedi Irawan (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2023)
The rapid information technology that is happening now has a significant impact on human life, including various activities that occur at the village office. The village head is responsible for managing funds at the village level including the collection and accountability of funds in accordance with the provisions of law no.33 of 2004 concerning the balance of central and regional governments. This study aims to implement a decision support system by combining two methods, namely the promethee and borda methods in selecting village budget plans in Tegal Sari village based on priority. The method used in this research is the Research and Development (R&D) method. The method used for calculations is the PROMETHEE and Borda methods. The PROMETHEE method is used to manage individual decisions from each decision maker, while the Borda method is used to manage group decisions resulting from the PROMETHEE ranking method. The criteria in this study are Cost, Completion Time, Impact on Regions/Society, Profits from Sustainable Investment, Factors of Interest. The results obtained from this research are Pemb. Health Sarpras as an alternative priority for the village budget.